2012
DOI: 10.4995/wrs.2012.1033
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of single nucleotide polymorphisms in the myosin VA (MYO5A) gene and its exclusion as the causative gene of the dilute coat colour locus in rabbit

Abstract: Classical genetic studies have identified different coat colour loci in rabbit and comparative analyses have established corresponding loci across species. In particular, the rabbit dilute locus is determined by a recessive coat colour mutation that modifies the basic colours influenced by the agouti and extension mutations. In mice, similar phenotypic effects are determined by a similarly named locus. This locus encodes the myosin VA (Myo5a) gene, whose protein product is an unconventional myosin that plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Considering the potential homology between the mouse and rabbit Dilute loci, the rabbit MYO5A gene was first investigated to evaluate if its mutations could be responsible for the coat color dilution observed in a few rabbit breeds, such as Vienna Blue. Fontanesi et al [72] excluded that the rabbit MYO5A gene was involved in determining the Dilute locus in this lagomorph species. Then, the rabbit melanophilin (MLPH) gene that in mice is responsible for a similar coat color phenotype determined by the Leaden locus [73] was investigated.…”
Section: Mutations In the Melanophilin (Mlph) Gene And The Dilute Locusmentioning
confidence: 98%
“…Considering the potential homology between the mouse and rabbit Dilute loci, the rabbit MYO5A gene was first investigated to evaluate if its mutations could be responsible for the coat color dilution observed in a few rabbit breeds, such as Vienna Blue. Fontanesi et al [72] excluded that the rabbit MYO5A gene was involved in determining the Dilute locus in this lagomorph species. Then, the rabbit melanophilin (MLPH) gene that in mice is responsible for a similar coat color phenotype determined by the Leaden locus [73] was investigated.…”
Section: Mutations In the Melanophilin (Mlph) Gene And The Dilute Locusmentioning
confidence: 98%
“…The action of the Myo5a gene has been quite well understood in other mammalian species, such as dogs, cats, mice, and rabbits [Searle 1968, Desnos et al 2007, Fontanesi et al 2012]. Some of these species have variations with brightened coat colour phenotypically similar to colours of mink, for example Russian blue in cats or Isabella in dogs -hence the decision to include the d allele in the genotypes.…”
Section: The Genotypesmentioning
confidence: 99%
“…In humans, mutations in the MLPH gene have been shown to cause Griscelli syndrome type III, which is an autosomal recessive disorder characterised by pigment dilution of the skin and hair (OMIM 609227) (Ménasché et al, 2003). Fontanesi et al first investigated the rabbit homologous gene of the mouse dilute locus and excluded MYO5A as the determinant of the dilute locus in rabbit (Fontanesi et al, 2012). After that, they found that a frameshift mutation in the MLPH gene (exon 5) causes the dilute coat colour in different rabbit (Oryctolagus cuniculus) breeds (Fontanesi et al, 2014).…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 99%